Enantioselective rhodium-catalysed insertion of trifluorodiazoethanes into tin hydrides - Hyde, S; Veliks, J; Ascough, D; Szpera, R; Paton, R; Gouverneur, V (Elsevier, 2018)
Aryl substituted 2,2,2-trifluorodiazoethanes undergo rhodium(II)-catalysed insertion reactions with tin hydrides affording the corresponding α-(trifluoromethyl)benzyl stannanes. This reactivity contrasts with that of diazo esters which predominantly afford CH2 reduction products in the presence of tin hydrides. The first example of asymmetric insertion into tin hydrides using diazo compounds is also described. In addition, this system extends to asymmetric germanium hydride and silane insertion.